Light energy transformation over a few nanometers. (23rd August 2017) - Huang, Hung Ji; Liu, Bo-Heng; Su, James; Chen, Po-Jui; Lin, Chun-Ting; Chiang, Hai-Pang; Kao, Tsung Sheng; Chau, Yuan-Fong Chou; Kei, Chi-Chung; Hwang, Chi-Hung
Abstract: Continuous platinum (Pt) thin film was fabricated via the plasma-enhanced atomic layer deposition method for a study of light energy transformation over a few nanometers. Light-to-heat experiments were used to determine the oscillating size effects on electromagnetic energy transformation in quantum wells of smooth and condensed Pt thin films. For Pt-film thicknesses of around 4 nm, 7 nm and 12 nm, electromagnetic heating presented unexpectedly high energy conversion efficiency. An empirical equation acquired from the fitting of the experimental data from various thicknesses of Pt thin films was suggested to describe the oscillating electromagnetic heating and quantized energy transformation. The experimental results show that size control of the nanostructures is extremely important for future applications involving quantum effects in nano devices.